Sustainability Analysis of Milkfish Farming in Traditional Ponds in Blandongan Village, Bugul Kidul Sub-District, Pasuruan City - Anggraeni, Ike Listya; Kartikaningsih, Hartati; Marhendra, Agung Pramana Warih (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Pasuruan City, located in East Java, plays a significant role in the fisheries sector, contributing to industrial and trade activities. However, production declines, influenced by poor water quality and flooding, threatens the sustainability of jelak milkfish farming. This study aims to analyze the status and sustainability index of the milkfish farming business using the MDS-Raps method, which evaluates it based on five dimensions: ecology, economy, social aspects, technology, and institutions. The respondents included 41 farmers from four fish farming groups (Pokdakan). The results shows that the business is fairly sustainable, with a multidimensional index of 51.99, meaning it can be continued and developed but does still has room for improvements. The sustainability status by dimension is as follows: ecological (65.24, fairly sustainable), economic (37.39, less sustainable), social (78.72, very sustainable), technological (27.40, less sustainable), and institutional (51.18, fairly sustainable). The study also proposes seven strategies to enhance sustainability and identifies a link between the MDS analysis and SWOT strategies in managing milkfish farming. Each SWOT strategy offers insights for improving the value of individual dimensions in the MDS framework.